Relationship between clinical and BK virological response in patients with late hemorrhagic cystitis treated with cidofovir: a retrospective study from the European Group for Blood and Marrow Transplantation - Cesaro, Simone; Pillon, M.; Tridello, G.; Aljurf, M.; Martino, R.; Schroyens, W.; Nozzoli, C.; Barba, P.; Faraci, M.; Fagioli, F.; Cappelli, B.; Cordonnier, C.; et al. (Bone marrow transplantation, 2013)
To investigate the relationship between clinical response and modification of BK viremia, we assessed retrospectively 32 cases of hemorrhagic cystitis (HC) after allogeneic hematopoietic SCT that were treated with i.v. cidofovir (CDV). They were 22 men (69%) and 10 women (31%) with a median age of 24 years, range 3-62. The median number of CDV doses was 3, range 1-8, and the treatment lasted for a median of 3 weeks, range 1-10. Clinical improvement of HC was observed in 27 patients (84%). In 12 of 32 episodes (37.5%), BK viremia was determined before every CDV administration and a complete clinical response was observed in 10 of 12 patients (83%), the reduction of BK viremia load being ⩾1 log by 2 weeks after starting CDV. Nephrotoxicity related to CDV was observed in nine patients. Among 26 patients with 100-day follow-up, 4 of 4 patients who had a complete clinical response by 30 days were alive vs 16 of 22 (73%) who did not have the resolution of HC in this time frame. We conclude that in patients with HC, the response to CDV treatment is usually associated with a significant reduction of BK viremia load.
Published online: 10 December 2012
Gesehen am 18.03.2021